Pengelolaan Sampah Plastik di Kawasan Pantai Depok, Kabupaten Bantul - Agya Zahra Salsabila; Fatma Ulfatun Najicha (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This study aims to determine the role of the environmental agency in managing plastic waste in the Depok Beach area and to find out the obstacles in managing plastic waste in the Depok Beach area. This research is a normative study, using secondary data in the form of primary, secondary and tertiary legal materials. To complete the above problems, this study uses empirical legal research methods. The conclusions in this legal research include the role of the environmental office in helping the Regent to carry out government affairs in the environmental sector. In addition, there are obstacles that affect the management of plastic waste in the Environmental Service.